Scientists in social encounters: the case for an engaged practice of science - Diaw, C.; Kusumanto, T. (Resources for the Future and Center for International Forestry Research, 2005)
In this chapter we questioned the link between conventional modes of knowledge extraction and local societies’ continuous marginality with regard to global knowledge and power networks. We reexamined the participatory, action and learning approaches intrinsic to adaptive collaborative management research in relation to forests. We also addressed the issues of interactivity, power, and science in participation. Using case studies from Indonesia and Cameroon, we illustrated how social science methods could go beyond just extracting information from local actors to serve as valid platforms for learning interactively and for negotiating meanings, powers, and representation. In that light, the scenarios that we see as the most promising lie with models of social facilitation in which scientific procedures are embedded into interactive methodologies to produce critical interactive knowledge.